Rancang Bangun Aplikasi Perangkat Lunak Absensi Digital dengan Keamanan Data untuk Politeknik Jakarta Internasional - Lanny Catrin Dale (Journal of Information Technology and Informatics Engineering, 2025)
This research was conducted by researchers to utilize design according to technological developments. Design is a process that defines something that will be done using various techniques and includes a description of the architecture and component details as well as the limitations that will be experienced in the process [1]. Design is a series of procedures to translate the results of analysis of a system into a programming language to describe in detail how the system components are implemented [2]. Data security is an effort to protect information from unauthorized access, use, disclosure, change, or destruction (M. Hadiwintata, 2020). According to Kristanto (2020/3) a Database Management System (DBMS) contains a collection of interrelated data and a set of programs to access that data. A database is a collection of interrelated files, the relationship is usually indicated by the key of each existing file (Kristanto, 2020). MySQL is a software or SQL database management system or DBMS that is multithreaded and multiuser (Solichin, 2005). Hypertext Preposessor is an abbreviation of PHP created by Rasmus Ledof in 1994, at the beginning of PHP development it was called an abbreviation of Personal Home Page (Antonius Nugraha, 1994). This research aims to design a fingerprint software for digital attendance with data security for the Jakarta International Polytechnic to make it easier for students, admins, lecturers and the director to do digital attendance. vehicle washing service business. application with Data Security for Jakarta International Polytechnic with Data Security for Jakarta International Polytechnic